IMPLEMENTASI UPAYA PROMOTIF TERKAIT COVID-19 DI RUMAH SAKIT UMUM DAERAH BUDHI ASIH TAHUN 2020 - Rizky Maulidiyah Harnum, (2021)
During the Covid-19 pandemic, health promotion are mandatory for all hospitals for Covid-19 prevention. However, implementing health promotion in hospitals have many obstacles. This also happened at the Budhi Asih Regional Hospital. The purpose of this study was to know how health promotion about Covid-19 implemented and the factors that influenced the implementation of health promotion about Covid-19 in Budhi Asih Regional Hospital in 2020. This study used qualitative research design with 10 informants. The tools used include question guidelines for indepth interviews, observation guidelines, and document teview guidelines. The analysis technique used is triangulation ofsources, methods, and theories. The results of the study stated that the Health Promotion at Budhi Asih Regional Hospital was not going well. This can be seen from the factors that influence it, such as the interest of the target group that have not been maximized and the availability of the resources is not enough. In addition, implementation during the Covid-19 pandemic experienced many obstackes. It is hoped that the hospital can fix all the factors that have not been carried out optimally.